2017
DOI: 10.1515/pjfns-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seasonal Variations in the Glucosinolate Content in Leaves and Roots of Four European Horseradish (Armoracia rusticana) Landraces

Abstract: In comparison with other cruciferous vegetables, horseradish has rarely been the object of scientifi c research, and the knowledge about the composition, content and distribution of glucosinolates (GLS) in different organs of horseradish plants is limited. Therefore, the aim of this study was to evaluate changes in the GLS content in leaves and roots of four horseradish landraces during the growing season.The presence of 13 GLS was determined in the examined horseradish tissues, and glucoraphanin, glucorapheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Seasonal variation in secondary metabolites has been documented repeatedly in above ground plant tissues (Bowers et al 1992;Carvalho et al 2014;Feeny 1970;Hare 2010;Liimatainen et al 2012;Riipi et al 2002). Several recent studies also demonstrate seasonal variability in secondary metabolites in below ground plant tissue (Ciska et al 2017;Robakowski et al 2016). Our results further support the notion that seasonal variation in defenses is common in below ground plant tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Seasonal variation in secondary metabolites has been documented repeatedly in above ground plant tissues (Bowers et al 1992;Carvalho et al 2014;Feeny 1970;Hare 2010;Liimatainen et al 2012;Riipi et al 2002). Several recent studies also demonstrate seasonal variability in secondary metabolites in below ground plant tissue (Ciska et al 2017;Robakowski et al 2016). Our results further support the notion that seasonal variation in defenses is common in below ground plant tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Probably in horseradish, the vitamin C was mobilized from the leaves to the roots during leaf senescence (D3) and back at the beginning of plant vegetative re-growth (D5). Variations of the content of other bioactive compounds, as the glucosinolates, throughout plant development of the two accessions tested in this study (Cor and Mon) have been reported by De Maria et al, (2016) and Rivelli et al, (2016a;2016b), as well as by Ciska et al, (2017) in other horseradish landraces.…”
Section: Variation Of Vitamin C Content In Leaves and Rootssupporting
confidence: 74%
“…To investigate this possibility, we performed a series of comparative feeding experiments with myrosinase-deficient and wild type Arabidopsis plants. In nature, P. armoraciae is closely associated with horseradish, Armoracia rusticana , a plant species that is characterized by high levels of allyl glucosinolate ( Li and Kushad, 2004 ; Ciska et al, 2017 ). Therefore, we additionally investigated the influence of plant myrosinase activity on the sequestration of allyl glucosinolate by spiking the intact glucosinolate into Arabidopsis leaves.…”
Section: Introductionmentioning
confidence: 99%